Criterios de éxito y no-éxito de la formación en el área de recursos humanos - SILVA PERALTA, Yamila Fernanda (Cuadernos de Estudios Empresariales, 2010)
The goal objective of this study was to investigate empirically success and non-success criteria starting from the content analysis of trainers’ critical incidents in human resources area. In first instance, theoretical approaches were explored starting from the analysis of scientific documents through PsycINFO Database (1978-2008) on the topic "Training evaluation in Human Resources area" (TEHR). These theoretical approaches were clustered in categories and used later on to code critical incidents content. From a theoretical point of view, this research evidences the growing importance of training as a process emphasizing in each of its phases and not reducing its evaluation to the results. However from the empiric analysis evaluation of training results is the major category which includes criteria related to trainer and trainee results.